Nano-bio interfaces effect of two-dimensional nanomaterials and their applications in cancer immunotherapy - Zhongmin Tang; Yufen Xiao; Na Kong; Chuang Liu; Wei Chen; Xiangang Huang; Daiyun Xu; Jiang Ouyang; Chan Feng; Cong Wang; Junqing Wang; Han Zhang; et al. (Elsevier, 2021)
The field of two-dimensional (2D) nanomaterial-based cancer immunotherapy combines research from multiple subdisciplines of material science, nano-chemistry, in particular nano-biological interactions, immunology, and medicinal chemistry. Most importantly, the "biological identity" of nanomaterials governed by bio-molecular corona in terms of bimolecular types, relative abundance, and conformation at the nanomaterial surface is now believed to influence blood circulation time, bio-distribution, immune response, cellular uptake, and intracellular trafficking. A better understanding of nano-bio interactions can improve utilization of 2D nano-architectures for cancer immunotherapy and immunotheranostics, allowing them to be adapted or modified to treat other immune dysregulation syndromes including autoimmune diseases or inflammation, infection, tissue regeneration, and transplantation. The manuscript reviews the biological interactions and immunotherapeutic applications of 2D nanomaterials, including understanding their interactions with biological molecules of the immune system, summarizes and prospects the applications of 2D nanomaterials in cancer immunotherapy.